Effects of solvent system and drying on the total phenolic content and antioxidant activities of leaf extract of Pereskia bleo. - Hwei Chyi Lui; Ai Ling Ho; Jau-Shya Lee; Pei-Teng Chan; Chee Kiong Siew (e-VIBS, Faculty of Science and Natural Resources, 2024)
Pereskia bleo (P. bleo), a plant traditionally consumed in parts of China, Malaysia, and Panama, is believed to have a variety of medicinal properties, including anti-cancer, anti-tumour, anti-rheumatic, anti-ulcer, and anti-inflammatory effects. The total phenolic content (TPC) and antioxidant activities of the leaves of P. bleo were determined using three extraction solvents of different polarities: water, methanol and dichloromethane. The effects of drying in a drying oven at 40˚C on the TPC and antioxidant activities were also determined. TPC was measured using the Folin-Ciocalteu reagent, and antioxidant activities were determined using ferric reducing antioxidant power (FRAP) assay and beta-carotene bleaching (BCB) assay. While the aqueous extract exhibited the highest TPC (p<0.05) (34.20 mg GAE/g extract for fresh leaves and 71.24 mg GAE/g extract for dried leaves), the methanolic extract showed the strongest antioxidant activities (p<0.05) for both the FRAP assay (332.17mmol Fe (II)/g extract for fresh leaves and 270.59 mmol Fe (II)/g extract for dried leaves) and the BCB assay (69.86% for fresh leaves and 60.50% for dried leaves). Drying resulted in a lower TPC (p<0.05) for the methanol and dichloromethane extractions (-5.39% and -15.67%, respectively) but an increased TPC (p<0.05) for the water extraction (+52.00%). The FRAP and BCB activities decreased (p<0.05) after drying, with reductions ranging from -12.82% to -34.53% and -13.31% to -65.52%, respectively.